Breakdown characteristics of polyethylene/silicon nitride nanocomposites - A. Azmi; K. A. A. Seman; K. Y. Lau (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Silicon nitride (Si3N4) has been utilized as a nanofiller in polymeric insulation due to its good characteristics in both electrical insulation and thermal conduction properties. In this work, a comparative study was performed between unfilled polyethylene and polyethylene containing different amounts of Si3N4 nanofiller. The study showed that the low density polyethylene (LDPE) added with 15 wt% of Si3N4nanofiller could have higher breakdown strength compared to equivalent LDPE with 10 wt% of Si3N4nanofiller. Morphological characterizations of the nanocomposite samples were performed using field emission electron microscopy (FESEM) and the results showed that the breakdown performance of the investigated materials were affected by the agglomeration of Si3N4 nanoparticles.